An Adaptive and Differentiated Digital Assessment Model to Measure Elementary Students' Character Values Using an Ethnosocial Approach in Science and Social Studies Learning - Asnawi; Ary Kiswanto Kenedi; Tengku Muhammad Sahudra; Dini Ramadhani; Asna Mardin (Jurnal Penelitian Pendidikan IPA, 2025)
Character assessment in science and social studies in elementary schools still faces various obstacles, particularly regarding the limited instruments available to accommodate differences in student characteristics and their social and cultural contexts. The main objective of this study was to develop a valid and effective Differentiated Adaptive Digital Assessment model to measure character values using an ethnosocial approach in elementary school students in science and social studies learning. This study used the Research and Development (R&D) method with the following stages: information gathering, model planning, prototype development, expert validation, preliminary field testing, and main field testing. Data were collected through interviews, observations, questionnaires, and documentation, and analyzed descriptively and inferentially. The results showed that the developed model was valid in content and construct and highly reliable (α > 0.85). All components of the model, from the character assessment rubric, ethno-social contextual tasks, adaptive digital platform, to the implementation guide, significantly contributed to measuring students' character values fairly and meaningfully. This study contributes to developing technology-based character assessment that is inclusive and culturally relevant at the elementary education level.